Increasing Student’s Civic Knowledge Through Schoology Based E-Learning - Dini Agnestin; Aim Abdulkarim; Rahmat Rahmat (Department of Civic Education, 2021)
This research based on the phenomenon of switching from conventional learning to full e-learning which is part of the impact of the physical distance policy in adapting to the Covid-19 pandemic situation. SMP Negeri 30 Bandung is one of the schools that uses Schoology as an alternative media for e-learning during the Covid-19 pandemic. Therefore, it is necessary to examine how the increase in civic knowledge of students through Schoology-based e-learning is related to the diversity of subjects in Citizenship Education subjects. The purpose of this study was to determine and analyze the increase in the civic knowledge of students through schoology-based e-learning as seen from the learning completeness of at least 70%. This type of research is sequential mixed methods using qualitative and quantitative approaches. The research sample used a random sampling technique to class VII students of SMP Negeri 30 Bandung for the academic year 2020/2021 with a total of 75 people. The results showed that the percentage of students' learning completeness was 70.7%, so it can be categorized as students who have completed learning individually and most of them have been able to achieve the Minimum Mastery Criteria (KKM).